Visuospatial perspective-taking of a protagonist during narrative comprehension: the effects of task load and individual differences in visuospatial working memory - Hosokawa, Asako; Kitagami, Shinji (Frontiers in Psychology, 2024)
This study examined whether visuospatial perspective uses the character perspective during narrative comprehension.Method: Participants read narrative stimuli depicting the spatial positional relationships between characters and objects and judged whether the objects were on the left or right from the character's perspective. We manipulated whether the spatial positional relationships between characters depicted in the narrative stimuli resulted in a visuospatial perspective. We hypothesized that the high-load perspective-taking condition would indicate longer reaction times compared to the low-load perspective-taking condition, as shifting perspectives between characters in the high-load condition require more time for visuospatial perspective-taking.Results: As predicted, the reaction time was longer for perspective-taking than for non-perspectivetaking.Discussion: During narrative comprehension, the reaction time for visuospatial perspective-taking must move virtually within the representation from the main character's perspective to that of another character. Visuospatial perspective-taking is involved in narrative comprehension.